Three-Dimensional Rotational Angiography during Catheterization of Congenital Heart Disease – A ten Years’ experience at a single center - Söder, Stephan; Wällisch, Wolfgang; Dittrich, Sven; Cesnjevar, Robert; Pfammatter, Jean Pierre; Glöckler, Martin (Scientific Reports, 2020)
This paper aims to assess the usability and advantages of three-dimensional rotational angiography (3DRA) in patients with congenital heart disease (CHD) and its application in the cath lab. Up to now, its use in CHD is not widespread or standardized. We analyzed all patients with CHD who underwent a 3DRA at our facility between January 2010 and May 2019. The 3DRAs were evaluated for radiation exposure, contrast dye consumption, diagnostic utility and image quality. We performed 872 3DRAs. 3DRA was used in 67.1% of the cases for interventional procedures and in 32.9% for diagnostic purposes. Two different acquisition programs were applied. The median dose-area product (DAP) for all 872 rotations was 54.1 µGym2 (21.7–147.5 µGym2) and 1.6 ml/kg (0.9–2.07 ml/kg) of contrast dye was used. Diagnostic utility of the generated 3D-model was rated superior to the native 3D angiography in 94% (819/872). 3DRA is an excellent and save diagnostic and interventional tool. However, 3DRA has not become a standard imaging procedure in pediatric cardiology up to now. Effort and advantage seems to be unbalanced, but new less invasive techniques may upgrade this method in future.
CRIS-Team Scopus Importer:2020-05-05